Conflicts of rights in the European Union : a theory of supranational adjudication - Torres Perez, Aida. (Oxford : Oxford University Press, 2009)
Underlying the protection of human rights in Europe is a complex network of legal systems - national, EU and ECHR. This book focuses on the potential for conflict to emerge between the systems in their interpretation of human rights, and presents a theory of international judicial dialogue to resolve conflicts.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Human rights -- European Union countries; Administrative procedure -- European Union countries; Judicial power -- European Union countries